Keadilan Substantif dalam Desentralisasi Asimetris: Perspektif Negara Hukum Pancasila - I Gde Sandy Satria (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The application of a uniform pattern in center-periphery relations is frequently entrapped in a rigidity of uniformity that neglects the sociological and historical complexities of Indonesian society. This study aims to analyze the juridical construction of asymmetric decentralization within the framework of the Pancasila Rule of Law, as well as its implications for the management of diversity and national integration. Employing a normative legal research method with conceptual and statutory approaches, this study reveals that asymmetric decentralization is not merely an administrative deviation, but rather an imperative manifestation of substantive justice and the politics of recognition towards regional particularities. Although this policy has been effective in mitigating disintegration potential in special regions such as Aceh and Papua, its implementation leaves residual issues regarding sharp disparities in authority, potential legal fragmentation, and inter-regional jealousy. This study concludes that the sustainability of special autonomy necessitates a governance reconstruction that is not solely oriented towards temporary political accommodation, but must be coherently integrated with Pancasila values. The theoretical implications of this study underscore the necessity for harmonization between national legal supremacy and the flexibility of regional autonomy to foster sustainable social cohesion within the Unitary State of the Republic of Indonesia.